The National Assessment of Educational Progress in Economics: Findings for General Economics - Walstad, William B; Buckles, Stephen (American Economic Review, 2008)
The National Assessment of Educational Progress in Economics: Findings for General Economics by William B. Walstad and Stephen Buckles. Published in volume 98, issue 2, pages 541-46 of American Economic Review, May 2008